(untitled) (Journal of the College of Basic Education, 2026)
This study investigates the natural radioactivity levels in ten commonly used medicinal herbs in Iraq to assess their radiological risks. The specific activity concentrations of naturally occurring radionuclides, including 238U, 232Th, and 40K, were measured using gamma-ray spectrometry with a high-purity germanium (HPGe) detector. The activity concentrations ranged from 1.79 to 22.94 Bq/kg for 238U, 0.55 to 5.5 Bq/kg for 232Th, and 6.3 to 421 Bq/kg for 40K. Radiological hazard indices, such as Radium equivalent activity (Raeq), Absorbed gamma dose rate(DƔ), Annual effective dose equivalent (AEDE), Activity gamma Index (Iɣ), external and internal hazard index (Hex, Hin), and Excess lifetime cancer risk (ELCR), were calculated to assess the potential health risks associated with consuming these herbs. The results indicate that all measured values are significantly lower than the global average limits recommended by UNSCEAR and ICRP, suggesting negligible radiological hazards. This study establishes baseline data for future evaluations of radiation exposure and affirms the safety of consuming these medicinal herbs.